2023
DOI: 10.1007/s40879-023-00659-4
|View full text |Cite
|
Sign up to set email alerts
|

Regular bi-interpretability of Chevalley groups over local rings

Abstract: In this paper we prove that if) is regularly bi-interpretable with the ring R. As a consequence of this theorem, we show that the class of all Chevalley groups over local rings (with the listed restrictions) is elementary definable, i. e., if for an arbitrary group H we have H ≡ G π (Φ, R), than there exists a ring R ′ ≡ R such that H ∼ = G π (Φ, R ′ ).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As it was observed in Section 1, Problem ( * ) has a positive solution for the Chevalley groups G P (Φ, R), when R is an algebraically closed field [68], when R is a Dedekind ring of the arithmetic type (can be deduced from [55]), and when is R is a local ring [14]. In the later two cases some mild invertability conditions on R are assumed.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…As it was observed in Section 1, Problem ( * ) has a positive solution for the Chevalley groups G P (Φ, R), when R is an algebraically closed field [68], when R is a Dedekind ring of the arithmetic type (can be deduced from [55]), and when is R is a local ring [14]. In the later two cases some mild invertability conditions on R are assumed.…”
Section: Resultsmentioning
confidence: 90%
“…D. Segal and K. Tent (see [55]) showed that for Chevalley groups G P (Φ, R) of rank > 1 over an integral domain R if G P (Φ, R) has finite elementary width or is adjoint, then G P (Φ, R) and R are bi-interpretable. In [14] it was proved that over local rings Chevalley groups G P (Φ, R) of rank > 1 are regularly bi-interpretable with the corresponding rings.…”
Section: Introduction Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation